Study on mitigating sediment and flood disasters with sand retarding basins in consideration of natural river environment - Ishikura Mikako; Kimura Ichiro; Harada Norio (E3S Web of Conferences)
“Sediment and Flood Disaster (SFD)” has recently been newly defined as a river disaster type. To mitigate SFD while considering river environment, sand retarding basins (SRB) are constructed upstream of the river for protection. In this study, we conducted laboratory experiments on the SRB to mitigate SFD and examine its fundamental aspects. Three types of SRB with different aspect ratios (B/b, where B is the width of the SRB and b is the width of the channel) were considered. Two experiments were conducted. In Case A, the water discharge was fixed at three different values, and the capture ratio of sand was measured 10 min after the start of discharge (quasi-equilibrium state). In Case B, the amount of sand in the SRB was measured every two minutes, thereby examining the temporal changes in the amount of sand deposited in the SRB. For B/b > 2, sand outflow was observed to slow down. For B/b > 3, a prolonged sand retention effect was observed.